2019
DOI: 10.1177/1087054719887433
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Visual and Auditory Attention Tests for Detecting ADHD

Abstract: Objective: This investigation examines the discriminative validity of visual and auditory attention tests for differentiating patients with ADHD from healthy control participants. Method: A total of 107 ADHD patients and 58 healthy control participants were recruited. Visual and auditory attention profiles were obtained using the Conners’ Continuous Performance Test 3rd Edition (CPT3) and Conners’ Continuous Auditory Test of Attention (CATA), respectively. Results: We found that ADHD patients underperformed he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…The severity and number of ADHD symptoms are associated with the degree of psychiatric comorbidity and disability, including cognitive abnormalities 47 . Cognitive domains commonly affected in ADHD include attention, working memory and problem solving 48 50 . As mental health issues may be neglected among athletes 51 , adverse symptoms, like neurocognitive deficits, may be present despite the lack of diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The severity and number of ADHD symptoms are associated with the degree of psychiatric comorbidity and disability, including cognitive abnormalities 47 . Cognitive domains commonly affected in ADHD include attention, working memory and problem solving 48 50 . As mental health issues may be neglected among athletes 51 , adverse symptoms, like neurocognitive deficits, may be present despite the lack of diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“… Data are expressed as N (%) or Mean ± SD. CPT3, the Conners' Continuous Performance Test 3rd Edition (Tu et al., 2018; Wang et al., 2021); ITS, internal transcribed spacer (Schoch et al., 2012); n/a, nonapplicable; SNAP‐IV, the Swanson, Nolan and Pelham Version IV Scale (Bussing et al., 2008; Gau et al., 2008, 2009); WISC‐IV, Wechsler Intelligence Scale for Children–Fourth Edition (Baron, 2005). …”
Section: Resultsmentioning
confidence: 99%
“…We adopted these two exams because they encompass both visual and auditory attention, which are the two most frequently impaired attentions in ADHD. Previous evidence has indicated that the CPT and CATA neuropsychological tests provide objective information about attention in ADHD cases [ 40 , 41 ]. The measures used in the analyses are omissions, commissions, and detectability (d’).…”
Section: Methodsmentioning
confidence: 99%